163k views
0 votes
What’s the answer?? need help

What’s the answer?? need help-example-1
User ConFusl
by
5.5k points

1 Answer

6 votes

Answer:

option A.


a^(9)b^(6)

Explanation:

To solve this, we need to use the following exponent rules:

Quotient rule: (a^n)/(a^m) = a^(n-m)

Power rule: (a^n)^m = a^nm

Power of a product rule: (ab)^n = (a^n)(b^n)

Then, we have the following expressions:


[(a^(-8)b)/(a^(-5) b^(3))}]^(-3)=[a^(-8+5)b^(1-3)}}]^(-3)=[a^(-3)b^(-2)]^(-3) =a^(9)b^(6)

So the correct result is option A.


a^(9)b^(6)

User Tamika
by
6.0k points